2020
DOI: 10.3390/sports8120157
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Inflammatory Cytokines and Irisin in Response to High Intensity Swimming in Adolescent versus Adult Male Swimmers

Abstract: Swimming is a popular youth sport that is considered beneficial for cardiovascular fitness. However, the potential inflammatory outcomes of high intensity swimming in younger swimmers are unclear, as is the response of irisin, a myokine released during exercise with anti-inflammatory properties. This study compared the plasma concentrations of interleukins 1-beta (IL-1β), 6 (IL-6), 10 (IL-10), tumor necrosis factor alpha (TNF-α) and irisin in response to intense swimming between adolescent and adult male swimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Adults showed a decrease in irisin level after swimming exercise, but the adolescent group did not show a change in irisin level. These results suggest adolescent athletes may have a blunted inflammatory and myokine response following exercise which may explain why young athletes require less recovery time from intense exercise (Table 6) [88].…”
Section: Role Of Irisin On Bone Homeostasis: Clinical Evidencementioning
confidence: 95%
“…Adults showed a decrease in irisin level after swimming exercise, but the adolescent group did not show a change in irisin level. These results suggest adolescent athletes may have a blunted inflammatory and myokine response following exercise which may explain why young athletes require less recovery time from intense exercise (Table 6) [88].…”
Section: Role Of Irisin On Bone Homeostasis: Clinical Evidencementioning
confidence: 95%
“…In the current study, significant increase (by 8%; p = 0.013) in circulating irisin level immediately after the aerobic rowing exercise was observed, while the increase was trivial (ES = 0.18) in magnitude in female rowers. Only few studies have investigated the response of irisin to acute exercise in athletes, and increases (Kabasakalis et al, 2020), no change (Vassalle et al, 2020;Joro et al, 2021) or even decreases (Sanderson et al, 2020) in irisin concentrations as a result of acute exercise have been observed. In contrast to our results, circulating irisin levels have been reported to be more sensitive to exercise intensity that is known to be an important stimulator for irisin release (Fatouros, 2018;Kabasakalis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These variables must be accounted for to understand the differences when assessing training programs and evaluating performance. Also, it should be noted that high-intensity interval exercise leads to different inflammatory markers in adult and adolescent swimmers [11]. Different effects of adult training content on adolescent athletes should also be considered.…”
Section: Introductionmentioning
confidence: 99%